(untitled) (Scientific journal of the Fergana State University, 2026)
In Uzbek literature, the psychophysiological condition of characters holds particular significance in the depiction of family relationships. The inner experiences and psychological states of the protagonists are reflected at the intersection of their external and internal worlds. This article analyzes the representations of the characters’ psychophysiological conditions within the familial relations portrayed in Said Ahmad’s short story “On the Roads Where Azrael Passed.”